The problem of evil : the Gifford lectures delivered in the University of St. Andrews in 2003 - Van Inwagen, Peter (Oxford University Press, 2008)
The vast amount of suffering in the world is often held as a particularly powerful reason to deny that God exists. Highly accessible and carefully argued, Peter van Inwagen's book maintains that such reasoning does not hold, and that suffering should not undermine belief in God. - ;It is generally supposed that the fact that the world contains a vast amount of suffering, much of it truly horrible suffering, confronts those who believe in an all-powerful and benevolent Creator with a serious problem: to explain why such a Creator would permit this. Many reflective people are convinced that the.